(2010) Modularization of korea's development experience : private sector development - Rhee, Zusun; Cho, Gyeong Lyeob; Lee, Taekyu (KDI School of Public Policy and Management, 2011)
In Korea, full-fledged industrialization policies began in 1961 when President Park Chunghee took office. During the course of industrialization, the most frequently utilized policies for corporate support included the finance and tax measures over which the government had a strong control. The financial support policies under the Park Administration included the export finance of the 1960s and the financial support for the heavy and chemical industries(HCIs) of the 1970s. For export finance, the automatic loan approval system played an important role. Additionally, export financing by the banks was supported by re-discount of the Bank of Korea. For the promotion of HCIs, policy loans were concentrated on the HCI sector, while the National Investment Fund(NIF) was established to utilize domestic savings for HCI investment. During the early stages of development, the financial supports were provided to the exporting companies, and the HCIs played a critical role in advancing industrialization of Korea in a short period. These policies also had served as a substitute for the underdeveloped financial market of the time. However, the Korean economy had to suffer from chronic inflation caused by monetary expansion as it developed. In addition, the government’s financial control also brought a harmful side effect that undermined the development of the financial industry. In the 1960s - the early stages of the industrialization - tax policy was focused on the increasing of tax revenues to secure the financial resources required for the economic development. While the corporate tax rate was maintained at high to increase tax revenues, various tax reduction schemes were also in places as incentives to boost exports. Entering 1970s when the government embarked on the policy to foster HCIs, the focus of tax policy shifted from direct taxes to indirect ones so that capital accumulation in the corporate sector could be accelerated. Especially, lowering the corporate tax rate was highly regarded as a significant contributor to the formation and the rapid growth of the private capital. In addition, the introduction of the value-added tax simplified consumption taxes and enhanced efficiency to a great extent, by improving the taxation neutrality among industries. On the other hand, the tax reduction and exemption system executed to nurture HCIs and to support exports has often been criticized to have caused an over-investment in HCIs via an inefficient allocation of resources among industries. At the turn of the 1980s, after the Park administration, the government policy began to prioritize the stability over the growth. With the change in the policy direction from growth to stability, the taarge of the policies to promote businesses was changed from large enterprises to the small-and-medium-ones, and is applicable until today. In terms of financial support to small-and-medium-sized enterprises(SMEs), some policies rely on market intervention like the regulation of mandatory lending by commercial banks to SMEs. But government support to SMEs is mostly provided through the policy loans. In order to promote SMEs, corporate tax benefits and support are also provided. The SME support system greatly contributed to the startups and the promotion of the SMEs, but came under criticism for emphasizing equity rather than efficiency resulting in another kind of inefficient resource allocation. Since the late 1990s, the government has focused its support on the venture businesses based on IT, the national strategic industry. In fostering the venture businesses, the policies also promoted equity financing through KOSDAQ. This approach was taken in order to spur risk sharing in the capital market and to expand the long-term fund for the venture business. Although the number of venture businesses increased exponentially, following these friendly measures, many of them went to bankruptcy due to the over-investment. As the result, the investors faced great financial losses at the consequent collapse of KOSDAQ market. Since then, the financial support system for venture businesses has relied less on direct support and has put greater emphasis on raising capital through “Fund of Funds(FOF)”. One of the remarkable policy changes since the 1980s is that the industry supportive policies shifted from the target-based, selective one to the function-based, general one. For industries that meet performance standards in terms of productivity improvement, energy strategy and etc., they were eligible for the same support. Therefore, policy support was not determined by the government but by the market, which resulted in substantially higher efficiency of the resource allocation. Furthermore, revolutionary tax support for venture businesses was introduced after the 1997 Asian Financial Crisis, which resulted in the growth of IT industries, venture capital, and the equity market(KOSDAQ). Meanwhile, even though various tax support measures were introduced temporarily with sunset provisions to promote venture businesses, the types of policy support continued to increase as time went on. Even after achieving the intended goals, a certain categories remained in the system. This implies that the venture businesses support system was not focused or selective, but rather impartial. Therefore, it resulted in the increased complexity in the tax system and the decreased tax base.
Keywords: Economic Policy